2006
DOI: 10.1088/0305-4470/39/31/010
|View full text |Cite
|
Sign up to set email alerts
|

Nonholonomic constraints with fractional derivatives

Abstract: We consider the fractional generalization of nonholonomic constraints defined by equations with fractional derivatives and provide some examples. The corresponding equations of motion are derived using variational principle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…As a further step, Riewe [1,2] formulated a version of the Euler-Lagrange equation for problems of calculus of variation with fractional derivatives. Recently, further studies concerning the fractional Euler-Lagrange equations can be found in the works of Agrawal and coworkers [5][6][7][8], Baleanu and coworkers [9][10][11][12][13][14][15], Tarasov and Zaslavsky [16,17] and others [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a further step, Riewe [1,2] formulated a version of the Euler-Lagrange equation for problems of calculus of variation with fractional derivatives. Recently, further studies concerning the fractional Euler-Lagrange equations can be found in the works of Agrawal and coworkers [5][6][7][8], Baleanu and coworkers [9][10][11][12][13][14][15], Tarasov and Zaslavsky [16,17] and others [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In last decades, much interest was devoted to apply fractional calculus to almost every field of science, engineering and mathematics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The awareness of the importance of this type of equation has grown continuously include for viscoelasticity and rheology, image processing, mechanics, mechatronics, physics, and control theory, see for instance [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the end of the 1970s, Mandelbrot [26] discovered that a large number of fractional dimension examples exists in nature. Since then, the study of the fractional dynamics has become a hot topic, and won wide development in theories and applications, including fractional Lagrangian mechanics, fractional Hamiltonian mechanics, fractional dynamics of nonholonomic system and fractional generalized Hamiltonian mechanics [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and their application [44][45][46][47][48][49][50]. In order to better solve the fractional dimension problems in science and engineering, it is necessary to propose a fractional dynamical theory of Birkhoffian systems.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible through a powerful tool known as the Euler-Lagrange equation [33]. Recently the theory of the calculus of variations has been considered in the fractional context [7,8,10,11,12,13,14,23,25,27,32]. The fractional calculus allows to generalize the ordinary differentiation and integration to an arbitrary (non-integer) order, and provides a powerful tool for modeling and solving various problems in science and engineering [28,29,31].…”
Section: Introductionmentioning
confidence: 99%